Sosialisasi Alur Pelayanan Rumah Sakit Desa Sisarahiligamo Kecamatan Gunung Sitoli Kota Gunung Sitoli - Meliala, Sri Agustina; Sulisna, Aida; Fitria, Dilla (Jurnal Abdimas Jatibara, 2024)
Hospital services, of course there are many complex problems that occur in the service process in hospitals to provide information systems that are expected to speed up services which will result in patient satisfaction. One of the problems is the registration flow process which often makes it difficult for people when they want to get health services at the hospital.  The government has attempted to do this by using the JKN mobile application, with mobile JKN, people no longer need to come to the hospital to register so that people can immediately get health services without queuing for registration at the hospital. However, if people want to receive inpatient services, they can reserve a room at the hospital without having to register directly at the hospital. The objective to provide knowledge, training and motivation to the community regarding the flow of hospital services. Method: present material and provide leaflets related to the flow of hospital services. The Results Increased public understanding regarding Digital-Based Health Services of the Social Security Administering Agency. Community service activities carried out with the title Socialization of hospital service flow in Sisarahiligamo village, Gunugsitoli District, Gunungsitoli City received good feedback from the community, especially the Sisarahiligamo community.